멀티플랫폼 시대 케이블 TV의 경쟁력 강화방안 - 유승관(Seung-Kwan Ryu); 안수근(Su-Keon An) (한국콘텐츠학회 논문지, 12(2), 2012)
This study investigated a current situation of cable TV in order to seek and suggest cable TV's competitive superiority in the era of multiplatform media marketplace. This study suggested cable TV's direction from two aspects, short-term and mid and long-term strategies. As a result, it recommended that cable TV industry need to establish content circulation representatives, and reinforce multiformat contents suitable for various multiplatform uses, digital cable promotion, production of SO's originated programs, HD VOD, bundling services and diverse programs. As a long-term strategy, this study also suggested cable TV industry need to cooperate with smart TV industry in order to widen openness of its platform, and to provide not only diverse contents but also applications by offering two-way, mobile, and on-demand contents and services. Finally, this study proposed cable TV is needed to move towards a comprehensive media portal, which is a contents aggregator with the aforementioned business strategies. 본 연구는 전반적인 케이블TV의 현황 고찰을 통해 멀티플랫폼 환경에서의 케이블TV의 경쟁력 제고를 위해 필요한 전략적 방안이 무엇인지에 대해 살펴보았다. 이를 위해 먼저 케이블TV의 현황, 특성 및 문제점을 살펴보고 이를 통해 매체경쟁력을 높일 수 있는 단기적, 중장기적 사업전략을 제언하였다. 케이블TV는 경쟁력 제고를 위해 콘텐츠 제작비 지원과 공동대표기구 설립, 멀티콘텐츠 포맷 개발 및 멀티 플랫폼 활용 활성화, 멀티미디어 환경에 대비한 뉴서비스 개발 및 제공, 자체제작을 통한 양질의 콘텐츠 확보, 디지털 케이블 확산, VOD 활성화, 결합서비스 강화, 프로그램 다양성 유지, 가격경쟁력 제고가 필요함을 제언하였다. 그리고 케이블TV의 경쟁력을 높이기 위한 장기적 방안으로 스마트TV와의 공조나 개방성 강화로 인한 오픈플랫폼전략 강화, 실시간 콘텐츠 이외에 사용자의 편의성을 높이는 양방형성, 이동성, 맞춤형 콘텐츠 개발을 통해 다양한 프로그램과 애플리케이션을 제공하는 어그리게이터(aggregator)의 기능 강화를 통한 종합미디어포털로 진화해야 할 것을 제언하였다.